الدور الوسيط للتوجه بالتعلم في العلاقة بين راس المال الفكري والإبداع الإداري في كبرى شركات المقاولات العاملة في قطاع غزة - الديراوي، أيمن حسن (جامعة الأقصى, 2021)
هدف البحث إلى اختبار الدور الوسيط للتوجه بالتعلم في العلاقة بين راس المال الفكري والإبداع الإداري في كبرى شركات المقاولات العاملة في قطاع غزة. وذلك عن طريق الاستثمار في الأصول الفكرية بهدف البقاء والاستمرار والمنافسة والنمو، وتم استخدام المنهج الوصفي التحليلي من خلال تطبيق أسلوب الحصر الشامل لكبرى شركات المقاولات في قطاع غزة وعددها (50) مفردة تم استرداد (39) استبانة بمعدل استجابة بلغت (78%). ومن أهم النتائج التي قدمها البحث: وجود أثر لجميع أبعاد راس المال الفكري على الإبداع الإداري في كبرى شركات المقاولات العاملة في قطاع غزة، مع تأكيد دور التوجه بالتعلم كوسيط ومعزز للأثر بين راس المال الفكري والإبداع الإداري. أما أهم التوصيات هي: ضرورة الاهتمام براس المال الفكري لأهميته في الإبداع للشركات، وإلزام العاملين بالتعلم المستمر مما يؤثر على راس المال الفكري.
The research aimed to test the mediating role of learning orientation m the relationship between intellectual capital and managerial creativity in major construction companies operating in the Gaza Strip. And that is by investing in intellectual assets in order to survive continue, competition and growth, and the descriptive analytical method was used through applying the comprehensive inventory method for major construction companies in the Gaza Strip amounting to (50) companies (39) questionnaires were retrieved with a response rate of (78%). The study concluded with a number of results: There is an effect of all the dimensions of intellectual capital on administrative creativity in the major construction companies operating in the Gaza Strip, with an emphasis on the role of learning orientation as a mediator and a reinforce of the impact between intellectual capital and administrative creativity. The study recommended a number of recommendations: The necessity of paying attention to intellectual capital due to its importance in the creativity of companies, and obliging employees to continuous learning, which affects intellectual capital.
Keywords: السياسة الإقتصادية -- راس المال الفكري -- الإبداع الإداري -- شركات المقاولات -- قطاع غزة